Evolution of bHLH transcription factors that control epidermal cell development in plants - Catarino, B (2017)
The colonization of the arid continental surface by plants was one of the milestones in Earth's history. Morphological innovations, such as the origin of complex 3D tissues, allowed the successful colonization and radiation of plants on land. The epidermis is the outermost plant tissue that constitutes the interface between the plant and the environment. Thus, the evolution of epidermal cells was crucial for the adaptation of plants on the terrestrial arid environment. I undertook a combined approach that aims to understand the evolutionary trends that drove land plant colonization and the genetic mechanisms that underlie the development of the epidermis. This approach includes: 1) analyses of plant transcription factors (TFs) families distribution and diversification, with a particular focus on the basic Helix-Loop-Helix (bHLH) TF family, and 2) functional characterization of a putatively conserved bHLH TF subfamily involved in epidermal cell development in land plants. Here, I showed that there was a stepwise increase in the number of transcription factor (TF) families and bHLH subfamilies that predated the colonization of the terrestrial surface by plants. The subsequent increase in TF number on land was through duplication within pre-existing TF families and subfamilies. Moreover, a similar trend occurred in metazoan bHLH TF, suggesting that the majority of innovation in plant and metazoan TF families occurred in the Precambrian before the Phanerozoic radiation of land plants and metazoans. Furthermore, I demonstrated that the function of IIIf bHLH TFs in controlling the development of the epidermal cell layer is conserved between liverworts and angiosperms. This suggests that IIIf bHLH TFs are ancient and conserved regulators of epidermal cell development since the early colonization of the land by plants. Moreover, these bHLH TFs were recruited during the evolution of land plants to control the development of seemingly unrelated morphological characters in specific lineages of extant land plants. The recruitment of ancient developmental regulators to control distinct and unrelated developmental processes in land plants might underlie the huge morphological and taxonomic radiation of plants on land.